The Cultivation of Cross-Cultural Communication Awareness in College English Teaching for Sports Majors and its Impact on Students’ Psychology - Wenjing Yao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In sports schools, it is worth exploring whether teachers attach importance to students' cross-cultural communication awareness, and whether the strategies and methods for cultivating cross-cultural communication awareness are in line with the characteristics of vocational school students. The author found through tests and questionnaires that the cross-cultural communication awareness of sports school students is still far from the actual needs of society and life, and there are significant deficiencies in learning motivation, cultural learning practice, and learning initiative. Through interviews with teachers, classroom observations, and analysis of English assignments and tests, several important constraints on cultivating cross-cultural communication awareness have been identified. Based on the theory and research of cross-cultural communication ability cultivation, combined with the characteristics of vocational school students, this article proposes the following strategies for cross-cultural English teaching in vocational schools. Teaching students according to their aptitude, promoting their understanding of cross-cultural communication needs, and increasing their enjoyment of learning cross-cultural communication; To create an atmosphere and increase cross-cultural experience opportunities for vocational school students, in addition to creating multiple cultural contexts in the classroom and forming a language and cultural integration model, sustainable cultural homework and testing should also be conducted outside of class. The significant progress of students requires our teachers to devote themselves to conducting more in-depth investigations and experiments, and to persistently use our patience and perseverance to assist our students in their growth. Of course, education and acting alone are not enough. We need to influence the people around us with our own ideas and learn from each other.